Auditory environmental context affects visual distance perception - Etchemendy, Pablo E.; Abregú, Ezequiel; Calcagno, Esteban R.; Eguia, Manuel C.; Vechiatti, Nilda; Iasi, Federico; Vergara, Ramiro O. (Scientific reports, 2017)
In this article, we show that visual distance perception (VDP) is influenced by the auditory environmental context through reverberation-related cues. We performed two VDP experiments in two dark rooms with extremely different reverberation times: an anechoic chamber and a reverberant room. Subjects assigned to the reverberant room perceived the targets farther than subjects assigned to the anechoic chamber. Also, we found a positive correlation between the maximum perceived distance and the auditorily perceived room size. We next performed a second experiment in which the same subjects of Experiment 1 were interchanged between rooms. We found that subjects preserved the responses from the previous experiment provided they were compatible with the present perception of the environment; if not, perceived distance was biased towards the auditorily perceived boundaries of the room. Results of both experiments show that the auditory environment can influence VDP, presumably through reverberation cues related to the perception of room size.